Simulação numérica de trocadores de calor multitubulares equipados com fitas helicoidais externamente aos tubos - Mansur, Sérgio Said [UNESP]; Mercier, Pierre (My University, 1998)
Classical shell-and-tube heat exchangers are usually equipped with segmental baffles. These baffles serve two basic functions: (a) they provide tube supports, thereby preventing or reducing mechanical problems, such as sagging or vibration; (b) they direct the fluid flow over the tubes so as to introduce a cross-flow component, thereby increasing the heat transfer. Segmented baffles have several sources of performance loss, some due to various leakage flows and others caused by stagnation zones. A new concept of longitudinal flow heat exchanger - based on placing twisted tapes along the tube bundle subchannels - was developed to mitigate drawbacks of other types of tubular heat exchangers. In this paper, a numerical model has been implemented in order to simulate the thermal-hydraulic feature of tubular heat exchangers equipped either with segmental baffles or with subchannel twisted tapes. The tube bundle has been described by means of an equivalent porous medium type model, allowing a macroscopic description of the shell-side flow. The basic equations - continuity, momentum and energy - have been solved by using the finite volume method. Typical numerical results have been compared with experimental data, reaching a very good agreement. A comparative analysis of different types of heat exchangers has been carried out, revealing the satisfactory thermal-hydraulic efficiency level of the twisted tapes heat exchangers.
Numerical simulation of multitubular heat exchangers equipped with twisted tapes outside the tubes
Keywords: Finite Volume Method; Flow Visualization; Heat Exchanger; Shell and Tubes; Twisted Tapes; Computational fluid dynamics; Computer simulation; Equations of motion; Finite volume method; Flow visualization; Mathematical models; Numerical analysis; Pipe flow; Multitubular heat exchangers; Segmental baffles; Subchannel twisted tapes; Heat exchangers